Self-locking mechanism for variable stiffness rigid-soft gripper - Guo, Xin-Yu; Li, Wen-Bo; Gao, Qiu-Hua; Yan, Han; Fei, Yan-Qiong; Zhang, Wen-Ming (Smart materials and structures, 2020)
Pneumatic soft grippers made of silicone have been successfully applied in the industrial field of grabbing fragile objects. But their inherent low stiffness often limits the practical application in scenarios required high stiffness or large load capacity. To expand the application of soft grippers, a self-locking mechanism realized by an exoskeleton structure is proposed in this work. The stiffness, load carrying capacity, and grabbing stability of this soft-rigid grippers can be enhanced in the premise of maintaining sufficient compliance. The resulted rigid-soft gripper has the ability of tuning its stiffness, simply by locking and unlocking the ratchet-and-pawl of the exoskeleton structure. The locking process is automatically implemented with the bending deformation of soft gripper, and the unlocking process is realized quickly by a simple pneumatic unlocking actuator. The stiffness, grasping motion and output force of the gripper are experimentally characterized theoretically and experimentally. And the capability of unlocking actuators is also verified and tested. Experimental results demonstrate that the rigid-soft gripper has a load capacity up to 9 kg. The gripper can achieve quick, flexible and reliable grasping for objects of various dimensions and shapes, with no compressed gas needed for holding. The proposed self-locking mechanism provides a simple but effective method to enhance the performance of soft grippers and simplify the operation for variable-stiffness grasping.